Personalized Automation of Treatment Planning for Linac-Based Stereotactic Body Radiotherapy of Spine Cancer - Cilla, Savino; Cellini, Francesco; Romano, Carmela; Macchia, Gabriella; Pezzulla, Donato; Viola, Pietro; Buwenge, Milly; Indovina, Luca; Valentini, Vincenzo; Morganti, Alessio G.; Deodato, Francesco (Frontiers in Oncology, 2022)
Purpose/Objective(s) Stereotactic ablative body radiotherapy (SBRT) for vertebral metastases is a challenging treatment process. Planning automation has recently reported the potential to improve plan quality and increase planning efficiency. We performed a dosimetric evaluation of the new Personalized engine implemented in Pinnacle3 for full planning automation of SBRT spine treatments in terms of plan quality, treatment efficiency, and delivery accuracy. Materials/Methods The Pinnacle3 treatment planning system was used to reoptimize six patients with spinal metastases, employing two separate automated engines. These two automated engines, the existing Autoplanning and the new Personalized, are both template-based algorithms that employ a wishlist to construct planning goals and an iterative technique to replicate the planning procedure performed by skilled planners. The boost tumor volume (BTV) was defined as the macroscopically visible lesion on RM examination, and the planning target volume (PTV) corresponds with the entire vertebra. Dose was prescribed according to simultaneous integrated boost strategy with BTV and PTV irradiated simultaneously over 3 fractions with a dose of 30 and 21 Gy, respectively. Dose-volume histogram (DVH) metrics and conformance indices were used to compare clinically accepted manual plans (MP) with automated plans developed using both Autoplanning (AP) and Personalized engines (Pers). All plans were evaluated for planning efficiency and dose delivery accuracy. Results For similar spinal cord sparing, automated plans reported a significant improvement of target coverage and dose conformity. On average, Pers plans increased near-minimal dose D98% by 10.4% and 8.9% and target coverage D95% by 8.0% and by 4.6% for BTV and PTV, respectively. Automated plans provided significantly superior dose conformity and dose contrast by 37%–47% and by 4.6%–5.7% compared with manual plans. Overall planning times were dramatically reduced to about 15 and 23 min for Pers and AP plans, respectively. The average beam-on times were found to be within 3 min for all plans. Despite the increased complexity, all plans passed the 2%/2 mm γ-analysis for dose verification. Conclusion Automated planning for spine SBRT through the new Pinnacle3 Personalized engine provided an overall increase of plan quality in terms of dose conformity and a major increase in efficiency. In this complex anatomical site, Personalized strongly reduce the tradeoff between optimal accurate dosimetry and planning time.